Electrolyte, secondary battery and electric equipment

By adding specific cosolvents to the lithium-ion battery electrolyte, more aggregated ion pair structures and LiF interface layers are formed, the problem of insufficient efficiency and circulation performance of lithium-ion battery is solved, and higher battery efficiency and longer service life.

CN119208738AActive Publication Date: 2024-12-27SUNWODA MOBILITY ENERGY TECHNOLOGY CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411134754.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-16
Publication Date
2024-12-27
Estimated Expiration
2044-08-16

AI Technical Summary

Technical Problem

The existing lithium-ion batteries have insufficient Coulomb efficiency and cycle performance, making it difficult to meet the electric vehicle industry's demand for high energy density and long cycle life.

Method used

Adding specific co-solvents to the electrolyte weakens the coordination effect of solvents and Li+, increases the coordination between anions and Li+, thereby forming more aggregated ion pair structures, improving the coulomb efficiency and cycle life of the battery, and co-solvents at the same time The F-containing functional groups form a LiF layer at the battery interface to improve cycling stability.

Benefits of technology

It significantly improves the Coulomb efficiency and circulation performance of lithium-ion batteries, extends the service life of the battery, and improves the circulation stability of the battery by forming a LiF interface layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208738A_ABST
    Figure CN119208738A_ABST
Patent Text Reader

Abstract

The invention provides an electrolyte, a secondary battery and electric equipment, and belongs to the technical field of new energy. The specific co-solvent is added into the electrolyte, so that the solvation ability of the electrolyte is weakened, the coordination effect of the solvent and Li < + > is reduced, the coordination competitiveness of the solvent and Li < + > is weakened, more anions are coordinated with Li < + >, more aggregated ion pairs are formed, the coulombic efficiency of the battery is improved, and the cycle service life of the battery is prolonged; meanwhile, the F-containing functional group of the cosolvent can form LiF interface layers on the negative electrode and the positive electrode of the battery, so that the cycle stability of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of new energy technology and relates to an electrolyte, a secondary battery and electrical equipment. Background Art

[0002] Lithium-ion batteries are widely used in electric vehicles and energy storage due to their high energy density, good cycle performance, fast charge and discharge, and environmental protection. In recent years, the rapid development of the electric vehicle industry has driven the development and progress of lithium-ion battery technology as the core of energy supply. The market has increasingly higher performance requirements for lithium-ion batteries, such as higher coulombic efficiency and better cycle performance. Therefore, it is necessary to develop a technology to effectively improve its coulombic efficiency and cycle performance. Summary of the invention

[0003] Based on the defects of the prior art, the purpose of this application is to provide an electrolyte, a secondary battery and an electrical device.

[0004] In order to achieve the above-mentioned object, in a first aspect, the present application provides an electrolyte comprising a main solvent, a co-solvent, a diluent and a lithium salt, wherein the co-solvent comprises at least one of the compounds of formula I,

[0005]

[0006] In formula I, x is an integer from 0 to 2.

[0007] In some embodiments, the co-solvent comprises at least one of a compound of formula A, a compound of formula B, and a compound of formula C,

[0008]

[0009] In some embodiments, the mass ratio of the main solvent, the co-solvent and the diluent is 1:(0.4-1.5):(5-12).

[0010] In some embodiments, the Raman spectrum of the electrolyte is between 745 and 760 cm -1 There are characteristic peaks of aggregated ion pair structure in the wavelength range.

[0011] In some embodiments, the aggregated ion pair content is ≥ 60%.

[0012] In some embodiments, the main solvent includes at least one of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and fluoroethylene carbonate.

[0013] In some embodiments, the diluent includes at least one of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, bis(2,2,2-trifluoroethyl ether), fluorobenzene, difluorobenzene, and trifluoromethoxybenzene.

[0014] In some embodiments, at least one of conditions S1 to S2 is satisfied:

[0015] S1. The lithium salt comprises at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonate), lithium tetrafluoroborate, lithium perchlorate and lithium trifluoromethanesulfonate;

[0016] S2. The concentration of the lithium salt in the electrolyte is 1-3 mol / L.

[0017] In a second aspect, a secondary battery is provided, which includes the electrolyte.

[0018] According to a third aspect, an electric device is provided, comprising the secondary battery, wherein the secondary battery is used as a power supply for the electric device.

[0019] Compared with the prior art, the present invention has the following beneficial effects: the present invention adds a specific co-solvent into the electrolyte to weaken the solvation capacity of the electrolyte and reduce the + The coordination effect weakens the solvent and Li + The competitive coordination makes more anions react with Li + Coordination can form more aggregated ion pairs (AGG) structures, thereby improving the coulombic efficiency and cycle life of the battery; at the same time, the F-containing functional groups of the co-solvent used can form a LiF interface layer at the negative and positive electrodes of the battery, which helps to improve the cycle stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is a synthetic route for the compound of formula I;

[0021] Figure 2 The H NMR spectrum and F NMR spectrum of DPE-F5 (i.e., the compound of formula C);

[0022] Figure 3 Comparison of the Coulombic efficiency of Li-Cu half-cells using GSE1 electrolyte and STD1 electrolyte;

[0023] Figure 4 This is a comparison of the cycling performance of Li-NCM single-layer soft-pack batteries using GSE1 electrolyte and STD1 electrolyte. DETAILED DESCRIPTION

[0024] In order to better illustrate the purpose, technical scheme and advantages of the present application, the present application will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present application in detail, rather than to limit the present application. All other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application. The experimental reagents and instruments involved in the implementation of this application are all commonly used ordinary reagents and instruments unless otherwise specified. In the present application, the technical features described in an open manner include closed technical schemes composed of the listed features, and also include open technical schemes containing the listed features.

[0025] The present application provides an electrolyte solution, comprising a main solvent, a co-solvent, a diluent and a lithium salt, wherein the co-solvent comprises at least one of the compounds of formula I,

[0026]

[0027] In formula I, x is an integer from 0 to 2.

[0028] In the present application, a specific co-solvent is added to the electrolyte, and its solvation ability is weaker than that of the main solvent. Therefore, its introduction will weaken the solvation ability of the electrolyte and reduce the solvent and Li + The coordination effect weakens the solvent and Li + The competitive coordination makes more anions react with Li + Coordinate to form more aggregated ion pairs (AGG) structures, thereby improving the coulombic efficiency and cycle life of the battery. In addition, the F-containing functional groups of the above co-solvents can form a LiF interface layer at the negative and positive electrodes of the battery, which helps to improve the cycle stability of the battery.

[0029] Due to the introduction of a specific co-solvent, the electrolyte of the present application has a higher content of aggregated ion pairs than traditional electrolytes with the same lithium salt concentration, thereby making the battery coulombic efficiency higher and the cycle performance better.

[0030] In some embodiments, the co-solvent comprises at least one of a compound of formula A, a compound of formula B, and a compound of formula C.

[0031]

[0032] When the above co-solvent includes at least one of the compounds of formula A, formula B and formula C, the content of aggregated ion pairs in the electrolyte is higher, the battery coulombic efficiency is higher, and the cycle performance is better. The compounds of formula A, formula B and formula C have an increasing effect on increasing the content of aggregated ion pairs in the electrolyte, an increasing effect on improving the battery coulombic efficiency, and an increasing effect on improving the battery cycle performance.

[0033] In some embodiments, the synthetic route for preparing the compound of formula I is as follows Figure 1 As shown, the following steps are included:

[0034] At -20 to 10° C., 4-toluenesulfonyl chloride, isopropoxyethanol and a basic catalyst are added to a first solvent, stirred to obtain a white suspension, and then extracted with a second solvent, and the solvent is removed from the organic layer obtained by extraction to obtain an intermediate product Ι (Ts-2-iPE);

[0035] At -20 to 10 °C, fluoroalcohol CF3CH (2-x) F x CH2OH (x is an integer of 0 to 2) and NaH are dissolved in a third solvent and stirred to react until no bubbles are generated to obtain sodium fluoroalkoxide CF3CH (2-x) F x CH2ONa, then add the intermediate product Ⅰ, heat the reaction to obtain a brown precipitate, then extract with a fourth solvent, remove the solvent from the organic layer obtained by extraction, and obtain the compound of formula Ⅰ.

[0036] In one embodiment, the alkaline catalyst includes at least one of KOH and NaOH.

[0037] In one embodiment, the molar ratio of 4-toluenesulfonyl chloride, isopropoxyethanol and the alkaline catalyst is (0.4-0.5):0.4:(0.4-0.5).

[0038] In one embodiment, the molar concentration of 4-toluenesulfonyl chloride in the first solvent is 1-2M.

[0039] In one embodiment, the first solvent includes at least one of dichloromethane and acetonitrile.

[0040] In one embodiment, the reaction of generating intermediate I using 4-toluenesulfonyl chloride and isopropoxyethanol is carried out in an ice bath.

[0041] In one embodiment, the reaction time of the reaction of using 4-toluenesulfonyl chloride and isopropoxyethanol to generate intermediate product I is 4 to 12 hours.

[0042] In one embodiment, during the preparation of intermediate product I, after extraction with a second solvent, the method of removing the solvent from the organic layer obtained by extraction includes rotary evaporation.

[0043] In one embodiment, the second solvent includes at least one of dichloromethane and acetonitrile.

[0044] In one embodiment, the fluoroalcohol CF3CH (2-x) F x CH2OH includes at least one of CF3CH2CH2OH, CF3CHFCH2OH, and CF3CF2CH2OH.

[0045] In one embodiment, the fluoroalcohol CF3CH (2-x) F x CH2OH and NaH generate sodium fluoroalkoxide CF3CH (2-x) F x The reaction of CH2Ona was carried out in an ice bath.

[0046] In one embodiment, sodium fluoroalkoxide CF3CH (2-x) F x CH2ONa includes at least one of CF3CH2CH2ONa, CF3CHFCH2ONa, and CF3CF2CH2ONa.

[0047] In one embodiment, the fluoroalcohol CF3CH (2-x) F x The molar ratio of CH2OH and NaH is 1:1.

[0048] In one embodiment, the molar concentration of the fluoroalcohol in the third solvent is 1-3M.

[0049] In one embodiment, the third solvent includes at least one of tetrahydrofuran (THF) and 2-methyltetrahydrofuran.

[0050] In one embodiment, the heating reaction is carried out at a temperature of 40 to 70° C. and for a time of 4 to 16 hours.

[0051] In one embodiment, the fourth solvent includes at least one of dichloromethane and acetonitrile.

[0052] In one embodiment, during the process of preparing the compound of formula I using the intermediate product I, after extraction with the fourth solvent, the method of removing the solvent from the organic layer obtained by extraction includes distillation under reduced pressure.

[0053] In one embodiment, the mass ratio of the main solvent, the co-solvent and the diluent is 1:(0.4-1.5):(5-12).

[0054] When the mass ratio of the main solvent to the co-solvent is within the range of 1:(0.4-1.5), such as 1:0.4, 1:0.6, 1:0.8, 1:1, 1:1.3, 1:5 or any two of the above values, while ensuring that the electrolyte has a higher ionic conductivity, it can induce more anions to react with Li + Coordination can form more aggregated ion pairs, which can improve the coulombic efficiency and cycle performance of the battery.

[0055] When the mass ratio of the main solvent to the diluent is within the range of 1:(5-12), such as 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12 or a range formed by any two of the above values, the electrolyte viscosity is better, the ionic conductivity is higher, and the main solvent can better play its role, thereby improving the coulombic efficiency and cycle performance of the battery.

[0056] In some embodiments, the mass fraction of the main solvent in the electrolyte is above 5%, such as 5%, 7%, 9%, 11%, 13%, 15%, 17%, 18%, 19%, 20% or a range formed by any two of the above values.

[0057] The Raman spectrum of the electrolyte is at 745-760 cm -1 There is a characteristic peak of the aggregated ion pair structure within the wavelength range. In some embodiments, the content of aggregated ion pairs is ≥ 60%, such as 60%, 62%, 64%, 66%, 68%, 70%, 72%, 75% or a range formed by any two of the above values. Wherein, the content of aggregated ion pairs = the peak area of ​​the characteristic peak of the aggregated ion pair structure in the Raman spectrum of the electrolyte / the peak area of ​​the characteristic peak of the lithium salt × 100%.

[0058] In some embodiments, the main solvent includes at least one of ethylene glycol dimethyl ether (DME), ethylene glycol diethyl ether (DEE), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and fluoroethylene carbonate (FEC).

[0059] In some embodiments, the diluent includes at least one of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether (TFE), bis(2,2,2-trifluoroethyl ether) (BTFE), fluorobenzene (FB), difluorobenzene (DFB), and trifluoromethoxybenzene (TFMB).

[0060] In some embodiments, the lithium salt includes at least one of lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium tetrafluoroborate, lithium perchlorate, and lithium trifluoromethanesulfonate.

[0061] In some embodiments, the concentration of lithium salt in the electrolyte is 1-3 mol / L, such as 1 mol / L, 1.2 mol / L, 1.4 mol / L, 1.6 mol / L, 18 mol / L, 2 mol / L, 2.2 mol / L, 2.4 mol / L, 2.6 mol / L, 2.8 mol / L, 3 mol / L or a range formed by any two of the above values. Even if the concentration of the above electrolyte is at a lower level, such as in the range of 1-3 mol / L, the content of aggregated ion pairs is higher than that of traditional high-salt electrolytes; at the same time, the lower concentration of lithium salt makes the viscosity of the electrolyte more suitable, the ion conductivity higher, and the cost lower.

[0062] The electrolyte may not contain other additives, or may contain other commonly used additives, such as fluorine-containing additives, nitrogen-containing additives, and self-polymerization additives. For example, the fluorine-containing additive includes at least one of fluoroethylene carbonate, dimethyl fluorocarbonate, fluoroformate, and lithium difluorooxalatoborate; the nitrogen-containing additive includes at least one of lithium nitrate, isosorbide nitrate, and trimethylsilane; and the self-polymerization additive includes at least one of dioxolane and trioxane.

[0063] In some embodiments, the method for preparing the electrolyte comprises the following steps:

[0064] Under an inert atmosphere, a main solvent, a co-solvent and a diluent are first mixed and dispersed to obtain a mixed solvent, and then a lithium salt is added to the obtained mixed solvent and dispersed to obtain an electrolyte.

[0065] The present application also provides a secondary battery, which includes the above electrolyte. The secondary battery has higher coulombic efficiency and better cycle performance due to the use of the above electrolyte.

[0066] The secondary battery also includes a negative electrode sheet. The present application has no particular restrictions on the negative electrode sheet, and any commonly used negative electrode sheet in the art can be used. In some embodiments, the negative electrode sheet includes a lithium metal negative electrode sheet. The lithium metal negative electrode has an ultra-high theoretical specific capacity (3860 mAh g -1 ) and low redox potential (-3.04 V vs. standard hydrogen electrode) and low density (0.534 g·cm -3), which is regarded as an ideal negative electrode in a lithium battery. However, the high chemical and electrochemical activity of lithium metal itself will cause harmful side reactions between the lithium metal negative electrode and the electrolyte, continuously consume lithium metal and electrolyte, and also cause uneven lithium deposition, leading to dendrite growth, increasing the specific surface area of ​​the lithium metal negative electrode, and accelerating the interface side reactions between the electrolyte and the electrolyte. The secondary batteries of these embodiments use the above-mentioned electrolyte to make the content of aggregated ion pairs in the electrolyte higher. The aggregated ion pairs will be reduced at the lithium metal negative electrode before the solvent, constructing a fast ion conduction SEI dominated by inorganic substances, inducing lithium to deposit more evenly, and improving the coulombic efficiency and cycle life of the battery; at the same time, the F-containing functional group of the co-solvent in the electrolyte can form a LiF interface layer at the negative and positive electrodes of the battery, which helps to improve the cycle stability of the battery.

[0067] The secondary battery also includes a positive electrode sheet. The present application has no particular restrictions on the positive electrode sheet, and any commonly used positive electrode sheet in the art can be used. In some embodiments, the positive electrode sheet includes a current collector and a positive electrode material layer disposed on at least one side of the current collector, the positive electrode material layer includes a ternary material, the ternary material includes at least one of lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide, and the molar amount of nickel element in the ternary material / the total molar amount of nickel element, cobalt element, manganese element and aluminum element is ≥ 0.8, such as 0.8, 0.82, 0.84, 0.86, 0.88, 0.90, 0.92, 0.94, 0.96 or a range formed by any two of the above values.

[0068] In some embodiments, the negative electrode plate includes a lithium metal negative electrode plate, the positive electrode plate includes a current collector and a positive electrode material layer disposed on at least one side of the current collector, the positive electrode material layer includes a ternary material, the ternary material includes at least one of lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide, and the molar amount of nickel element in the ternary material / the total molar amount of nickel element, cobalt element, manganese element and aluminum element is ≥ 0.8 (such as 0.8, 0.82, 0.84, 0.86, 0.88, 0.90, 0.92, 0.94, 0.96 or a range formed by any two of the above values). The secondary batteries of these embodiments achieve stable battery cycling in the voltage range of 2.5-4.25V.

[0069] The secondary battery also includes a diaphragm, which is located between the positive electrode sheet and the negative electrode sheet, and is used to separate the positive electrode sheet and the negative electrode sheet to prevent the positive electrode sheet and the negative electrode sheet from contacting and short-circuiting. The present application has no particular restrictions on the diaphragm, and any commonly used diaphragm in the art can be used. In some embodiments, the diaphragm includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, etc.

[0070] The present application also provides an electrical device, comprising the secondary battery mentioned above, wherein the secondary battery is used as a power supply for the electrical device.

[0071] The present application is further described below by means of specific examples, wherein the co-solvent DPE-F x+3 The preparation method is as follows:

[0072] DPE-F5 (i.e., compound of formula C): 0.44 mol 4-toluenesulfonyl chloride (Ts-Cl), 0.5 mol potassium hydroxide and 0.4 mol isopropoxyethanol (2-iPE) were added to 250 mL dichloromethane under ice bath conditions, and stirred for 4 h to obtain a white suspension, which was extracted with dichloromethane, and the organic layer obtained by extraction was rotary evaporated to obtain the intermediate product I (Ts-2-iPE), with a yield of >98% (mol / mol, the same below);

[0073] Under ice bath conditions, 0.4 mol of fluoroalcohol CF3CF2CH2OH and 0.4 mol of NaH were dissolved in 150 mL of THF solvent, and the reaction was stirred until no bubbles were generated to obtain sodium fluoroalcohol CF3CF2CH2ONa. Then 0.4 mol of intermediate product I was added, and the reaction was heated at 60°C for 12 h to obtain a brown precipitate. The precipitate was extracted with dichloromethane, and the organic layer obtained by the extraction was distilled under reduced pressure to obtain the final product DPE-F5 with a yield of >95%.

[0074] DPE-F4 (i.e., compound of formula B): The difference between the preparation method of DPE-F5 and that of DPE-F4 is that the co-solvent DPE-F x+3 During the process, an equal molar amount of fluoroalcohol CF3CHFCH2OH was used to replace fluoroalcohol CF3CF2CH2OH, and the yield of DPE-F4 was >95%.

[0075] DPE-F3 (i.e., compound of formula A): The difference between the preparation method of DPE-F5 and that of DPE-F5 is that the co-solvent DPE-F x+3 During the process, an equal molar amount of fluoroalcohol CF3CH2CH2OH was used to replace fluoroalcohol CF3CF2CH2OH, and the yield of DPE-F4 was >95%.

[0076] Example 1

[0077] At 25°C, in a glove box filled with argon (H2O<1ppm, O2<1ppm), the main solvent, co-solvent and diluent were measured respectively in a mass ratio of main solvent: co-solvent: diluent = 1.5:1:12, and stirred to obtain a mixed solvent. Then 1L of the mixed solvent was added with 1.5 mol LiFSI, and stirred until completely dissolved to obtain an electrolyte, wherein the main solvent was ethylene glycol dimethyl ether (DME), the co-solvent was DPE-F5, and the diluent was 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE).

[0078] Embodiments 2 to 9

[0079] The difference from Example 1 is that the mass ratios of the main solvent, co-solvent and diluent used in the preparation of the electrolyte are different, see Table 1 for details.

[0080] Embodiments 10 to 12

[0081] The difference from Example 1 is that the mass ratio of the main solvent, co-solvent and diluent used in the preparation of the electrolyte (if any) and the lithium salt concentration in the electrolyte are different, see Table 1 for details.

[0082] Embodiments 13-14

[0083] The difference from Example 1 is that the types of co-solvents used in the preparation of the electrolyte are different, see Table 1 for details.

[0084] Embodiments 15-16

[0085] The difference from Example 1 is that the type of diluent used in the process of preparing the electrolyte and the mass ratio of the main solvent, co-solvent and diluent used are different, see Table 1 for details.

[0086] Examples 17 to 21

[0087] The difference from Example 1 is that the types of main solvents, and / or diluents, and / or lithium salts used in the process of preparing the electrolyte are different, see Table 1 for details.

[0088] Comparative Example 1

[0089] The difference from Example 1 is that no co-solvent is used in the process of preparing the electrolyte, and the mass ratio of the main solvent to the diluent is different, see Table 1 for details.

[0090] Comparative Example 2

[0091] The difference from Example 1 is that no diluent is used in the process of preparing the electrolyte, see Table 1 for details.

[0092] Comparative Example 3

[0093] The difference from Example 1 is that no diluent is used in the process of preparing the electrolyte, and the concentration of lithium salt in the electrolyte is different, see Table 1 for details.

[0094] Comparative Example 4

[0095] The difference from Example 1 is that the type of co-solvent used in the preparation of the electrolyte is different. The co-solvent used in this comparative example is (CH3)2CHOCH2OCH2CH2CF3(TFMPP), and the structural formula is as follows:

[0096]

[0097] The electrolytes obtained in Examples 1 to 21 are respectively recorded as GSE1 electrolyte, GSE2 electrolyte, GSE3 electrolyte...GSE21 electrolyte (i.e., the electrolyte obtained in Example x is recorded as GSEx electrolyte); the electrolytes obtained in Comparative Examples 1 to 4 are respectively recorded as STD1 electrolyte, STD2 electrolyte, STD3 electrolyte, and STD4 electrolyte.

[0098] Test Case

[0099] The electrolytes obtained in the above embodiments and comparative examples were subjected to the following performance tests:

[0100] (1) MRI test

[0101] Take 0.05mL DPE-F x+3 A series of solvents were mixed with 0.5 mL of deuterated chloroform, dispersed, injected into the NMR tube and sealed, and then tested for H NMR and F NMR spectra. The test results of DPE-F5 solvent are shown in Figure 2. Figure 2 shown.

[0102] (2) Test of AGG content in electrolyte

[0103] A small amount of electrolyte was drawn by capillary tube for Raman spectroscopy characterization. The results of the analysis showed that the peak at about 750 cm -1 The characteristic peak of aggregated ion pair structure (AGG) was detected and the AGG content was quantitatively obtained.

[0104] (3) Average Coulomb efficiency test

[0105] A 6 μm copper foil was cut into pieces to obtain a copper counter electrode. The prepared copper counter electrode, a diaphragm (a PP diaphragm was used for the diaphragm), and a 200 μm lithium metal negative electrode were stacked in order and placed in a battery shell. 30 μL of electrolyte was added dropwise with a pipette gun. A button battery sealing machine was used to pressurize and package the battery at a pressure of 30 KPa to prepare a lithium-copper half-cell. The obtained lithium-copper half-cell was then subjected to a coulombic efficiency test. The specific test method was as follows: the lithium-copper half-cell was subjected to a 1 mA·cm -2 At a current density of 3 mAh·cm -2 Lithium to copper current collector, charged to 1V, record stripped lithium capacity of C1mAh·cm -2 , Coulomb efficiency CE1% = C1 / 3 × 100%; repeat this cycle 50 times, and calculate the average Coulomb efficiency CE from the 6th to the 50th cycle Ave. %, where the coulombic efficiencies in GSE1 and STD1 electrolytes are as follows Figure 3 shown.

[0106] (4) Battery cycle stability test

[0107] The positive electrode active material LiNi 0.92 Co0.07 Mn 0.01 O2 (NCM), conductive agent acetylene black (Super P) and binder polyvinylidene fluoride (PVDF) are LiNi 0.92 Co 0.07 Mn 0.01 O2:Super P:PVDF=90:6:4 was mixed evenly and dispersed in 1-methyl-2-pyrrolidone (NMP) to form a black slurry. The obtained black slurry was coated on both sides of the aluminum foil, baked, rolled and cut into pieces to obtain the positive electrode sheet. The positive electrode surface capacity was 4.5mAh / cm 2 ;

[0108] The prepared positive electrode sheet, separator (PP separator) and 20μm lithium metal negative electrode sheet are stacked in order so that each positive electrode membrane layer and negative electrode membrane layer are covered with a separator, and then stacked into a battery cell, hot pressed, welded to the pole ear and loaded into an outer packaging shell, and then baked and dried, and injected with GSE1 electrolyte, with an injection volume of 2g / Ah, and then subjected to standing, formation, aging, and volume separation to prepare a single-layer soft-pack lithium-high nickel ternary full battery;

[0109] The single-layer soft-pack lithium-high nickel ternary full battery was charged and discharged at 25°C, with a charge rate of 0.5C, a discharge rate of 0.2C, and a voltage range of 2.5-4.25V. The capacity retention rate of the nth cycle was recorded as the discharge capacity of the nth cycle / the discharge capacity of the first cycle × 100%. When the capacity retention rate decays to 80%, the number of cycles is the battery cycle life.

[0110] The test results are shown in Table 1.

[0111] Table 1

[0112]

[0113]

[0114] It can be seen from the above data that the electrolyte of each embodiment of the present application has a high AGG content, and the battery used has a high coulombic efficiency and good cycle performance. For example, the AGG content is above 60%, the average coulombic efficiency is above 99.10%, and the cycle life is above 80 cycles.

[0115] From the comparison of Examples 1 to 5, it can be seen that the mass ratio of the main solvent to the co-solvent will affect the AGG content, average coulombic efficiency and cycle life in the electrolyte. When the mass ratio of the two is in the range of 1:(0.4-1.5), the AGG content in the electrolyte is higher, the average coulombic efficiency is higher, and the cycle life is longer.

[0116] From the comparison of Examples 1 to 9, it can be seen that the mass ratio of the main solvent to the diluent affects the AGG content, average coulombic efficiency and cycle life in the electrolyte. When the mass ratio of the two is in the range of 1:(5-12), the AGG content in the electrolyte is higher, the average coulombic efficiency is higher, and the cycle life is longer.

[0117] Since the electrolyte of Comparative Example 1 does not contain a co-solvent, the AGG content is relatively low, the average coulombic efficiency is relatively low, and the cycle life is relatively short.

[0118] Since the electrolyte of Comparative Examples 2 to 3 does not contain a diluent, even if the lithium salt concentration is increased to make the AGG content in the electrolyte higher, the average coulomb efficiency is still low and the cycle life is still short.

[0119] In Comparative Example 4, due to the use of other co-solvents, the AGG content in the electrolyte is relatively low, the average coulombic efficiency is relatively low, and the cycle life is relatively short.

[0120] Depend on Figure 3 It can be seen that compared with the electrolyte of comparative example 1, the coulombic efficiency of the electrolyte of embodiment 1 is higher. Figure 4 It can be seen that compared with the electrolyte of Comparative Example 1, the electrolyte of Example 1 has better cycle performance.

[0121] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.

Claims

1. An electrolyte, characterized in that: It comprises a main solvent, a co-solvent, a diluent and a lithium salt, wherein the co-solvent comprises at least one of the compounds of formula I, In formula I, x is an integer from 0 to 2.

2. The electrolyte according to claim 1, characterized in that The co-solvent comprises at least one of a compound of formula A, a compound of formula B and a compound of formula C, 3. The electrolyte according to claim 1, characterized in that The mass ratio of the main solvent, the co-solvent and the diluent is 1:(0.4-1.5):(5-12).

4. The electrolyte according to claim 1, characterized in that The Raman spectrum of the electrolyte is between 745 and 760 cm -1 There are characteristic peaks of aggregated ion pair structure in the wavelength range.

5. The electrolyte according to claim 4, characterized in that The content of aggregated ion pairs is ≥ 60%.

6. The electrolyte according to claim 1, characterized in that The main solvent includes at least one of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and fluoroethylene carbonate.

7. The electrolyte according to claim 1, characterized in that The diluent includes at least one of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, bis(2,2,2-trifluoroethyl ether), fluorobenzene, difluorobenzene and trifluoromethoxybenzene.

8. The electrolyte according to claim 1, characterized in that At least one of the conditions S1 to S2 is met: S1. The lithium salt comprises at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonate), lithium tetrafluoroborate, lithium perchlorate and lithium trifluoromethanesulfonate; S2. The concentration of the lithium salt in the electrolyte is 1-3 mol / L.

9. A secondary battery, characterized in that: The invention comprises the electrolyte as claimed in any one of claims 1 to 8.

10. An electrical device, characterized in that: The secondary battery as claimed in claim 9 is used as a power supply for the electric device.

Citation Information

Patent Citations

  • Ether electrolyte and lithium-sulfur secondary battery

    CN110416597A

  • Low-concentration lithium ion battery electrolyte and lithium ion battery prepared from same

    CN114024036A

  • Lithium-sulfur battery electrolyte and lithium-sulfur battery

    CN116344932A

  • Ether-based electrolyte and preparation method thereof

    CN117276678A

  • Electrolyte solvent, lithium metal battery electrolyte and lithium metal battery

    CN117317378A